ANALYSIS IMPACT OF TRAFFIC (ANDALALIN) KAWASAN MALL TRANSMART OF TAJUR ROAD BOGOR - Aldiansyah, Muhamad (ASTONJADRO, 2022)
East Bogor District has 6 Village Office with an area of 10.15km2. The increase in population growth and development in the area has also increased the movement of traffic flow into and out of the area, causing several problems especially in reducing the performance of road sections that cause traffic congestion on road sections. This study aims to create a model of the generation and attraction generated by land uses such as the Education Building, Industrial Estate, Traditional Markets and Supermarkets. Located in the district. Data processing is carried out with the calculation method of transportation analysis using MKJI 2017. Then it uses (Trip Generation Manual) and then modeled in (Saturn Software). The number of Stitches and Pulls in the area studied was found to be 91.82 trips / hour. With the level of road services with a range of C to F. Then the design equation of transportation modeling for East Bogor sub-district in 2019 is Y = 11,790 + 1,098 (X) then in 2025, Y = 2963.66 + 0.840 (X). This proves that if there is no improvement and improvement of road network infrastructure, and efforts to procure an adequate road-based mass public transport system, it will add to the decline in performance of road segments in the region in the future.